Planejamento e gestão orçamentária para busca de eficiência das políticas públicas: análise da educação fundamental I dos municípios da microrregião de Pato Branco - Malagi, Cleverson (2025)
The research analyzes how budget planning and management instruments impact the efficiency of public policies in general, that is, across all areas of government activity, with a special emphasis on basic education, specifically in the early grades of elementary school (1st to 5th grade), in the municipalities of the Pato Branco microregion in southwestern Paraná, from 2019 to 2023. The premise is that budget planning, when properly implemented, contributes to improving educational indicators and, consequently, regional development. The study's overall objective is to demonstrate whether the correct use of planning and management instruments, based on government functions and subfunctions, positively influences the quality of public education and impacts other municipal development indicators. The methodology adopted combines qualitative and quantitative approaches, both applied and exploratory in nature, and is structured in four phases: bibliographic and documentary survey, budget execution analysis, assessment of budget efficiency correlated with educational and socioeconomic indicators, and, finally, proposal of guidelines. Secondary data from the IDEB (National Institute of Geography and Statistics), IPDM (National Institute of Geography and Statistics), IBGE (Brazilian Institute of Geography and Statistics), budget execution reports, and official documents from each municipality studied were used, analyzed using descriptive statistics, correlation analysis, linear regression, and the construction of budget efficiency indices. The results indicate that municipalities that demonstrated greater adherence to efficient budget planning and execution practices, particularly in education, also achieved better performance in the IDEB (National Institute of Geography and Statistics) and positive impacts on social development, income, and health indicators. The research demonstrates that efficient allocation of public resources is directly associated with responsible governance, rigorous application of budget management instruments, and the integration of public policies. It is concluded that strengthening fiscal planning and management mechanisms, combined with prioritizing education, constitutes a strategic vector for promoting regional development, offering a methodology applicable to other territories with similar characteristics.